Comparison of postmortem changes in ATP-related compounds, protein degradation and endogenous enzyme activity of white muscle and dark muscle from common carp (Cyprinus carpio) stored at 4 °C. (May 2017) - Li, Qian; Zhang, Longteng; Lu, Han; Song, Sijia; Luo, Yongkang
Abstract: Postmortem changes in white muscle and dark muscle of common carp ( Cyprinus carpio ) during 72 h at 4 °C were evaluated by determining ATP-related compounds, AMP-deaminase (ADA) activity, acid phosphatase (ACP) activity, pH, texture properties, contents and SDS-PAGE patterns of myofibrillar and sarcoplasmic proteins, as well as activity of cathepsins B and B + L. The results showed that white muscle had a significantly ( P  < 0.05) higher pH and inosine monophosphate (IMP) concentration but a lower hardness after slaughter. Higher activity of ADA and ACP in dark muscle coincided with its higher K value. The SDS-PAGE patterns showed that white muscle contained more protein bands for myofibrillar and sarcoplasmic proteins, while dark muscle had more bands with low molecular weights for sarcoplasmic protein. Cathepsins B and B + L showed higher activity in dark muscle than in white muscle, especially at the later period of storage. Higher activity of endogenous enzymes in dark muscle might contribute to its faster quality loss. Highlights: Postmortem changes in white and dark muscles of carp were investigated. Dark muscle had a lower content of IMP and a higher K value. Activities of ADA, ACP, cathepsins B and B + L were higher in dark muscle.